Productivity and Psychology Well - Moch. Anas Bachtiar; M. Isa Anshori (Pusat Riset dan Inovasi Nasional, 2024)
Increasing employee work productivity is a major concern for companies. Its decline can be fatal to the company's profits and survival. Therefore, this literature study was made to understand the concept of psychological well-being and how its application can increase employee work productivity. This research uses the literature review method or literature review. This method is systematic, specific, and consistent in conducting in-depth identification of various sources of information. This literature study resulted in findings that the dimensions of psychology and employee productivity have a close relationship and influence each other. A good psychological dimension can increase motivation, focus, creativity, teamwork, and employee job satisfaction, which ultimately has an impact on increasing productivity. Conversely, a bad psychological dimension can reduce all these factors and result in decreased productivity.